2015
DOI: 10.1002/art.39138
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Autocrine Cytokine–Mediated Deficiency of TRAIL‐Induced Monocyte Apoptosis in Rheumatoid Arthritis

Abstract: Objective Dysregulated apoptosis of monocytes is a pathogenic feature of rheumatoid arthritis (RA). The aim of this study was to investigate the role of TRAIL and TRAIL‐induced apoptosis in patients with RA. Methods Cell surface expression and serum concentrations of TRAIL were determined in 63 patients with RA, and TRAIL‐induced monocyte apoptosis was quantified. Surface expression of TRAILR‐1, TRAILR‐2, TRAILR‐3, TRAILR‐4, CXCR1, and CXCR2 was determined, and intracellular signal transduction was investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…After dust entered the alveoli, AMs were activated by phagocytosis of dust particles, and caspase‐dependent apoptosis occurred (Bai et al, ). Apoptosis may be initiated through the cell surface receptor of AM with its ligand combination, which is mainly achieved through the induction of apoptosis in three basic signal transduction pathways: Fas–Fas‐L pathway, TNF‐α–TNFR pathway, and TRAILR–TRAIL pathway (Lin et al, ; Meusch et al, ; Zhang et al, ). AMs are key regulatory cells in lung; however, the role of apoptotic AM in lung inflammatory and fibrotic lung disorders remains to be well characterized (L. Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…After dust entered the alveoli, AMs were activated by phagocytosis of dust particles, and caspase‐dependent apoptosis occurred (Bai et al, ). Apoptosis may be initiated through the cell surface receptor of AM with its ligand combination, which is mainly achieved through the induction of apoptosis in three basic signal transduction pathways: Fas–Fas‐L pathway, TNF‐α–TNFR pathway, and TRAILR–TRAIL pathway (Lin et al, ; Meusch et al, ; Zhang et al, ). AMs are key regulatory cells in lung; however, the role of apoptotic AM in lung inflammatory and fibrotic lung disorders remains to be well characterized (L. Wang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The CpG islands in the promoter region of the DR3 gene were hypermethylated, where inverse correlation existed in the levels of serum DR3 protein and promoter CpG methylation in rheumatoid synovia ( 60 ). In relationship to DR3, TRAIL-induced apoptosis has been shown to be defective in the monocytes of RA patients ( 60 ), and the decoy receptor 3 that protects cells from Fas-induced apoptosis was also over-represented in RA ( 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the first study case, on the one hand, we found that the differentially expressed genes (such as CREB1 [ 42 , 43 ], TNFSF10 [ 44 ], CD4 [ 45 ], and TNFSF12 [ 46 ]), and the non-differentially expressed genes (such as ESR1 [ 47 ], VDR [ 48 ], PPARG [ 49 ], ESR2 [ 50 ]) are RA-related genes. On the other hand, we also found that some of the hub nodes in the network are not included in the RA-related gene dataset, such as differentially expressed genes GSK3B , SMARCA4 , PSMD7 , TGFBR1 , and so forth, and non-differentially expressed genes HNF4A , PGR , RXRA , ESRRA , and so forth.…”
Section: Discussionmentioning
confidence: 99%